A functionalized membrane for lithium–oxygen batteries to suppress the shuttle effect of redox mediators. Issue 23 (31st May 2019) - Chen, Zi-Fang; Lin, Xiaodong; Xia, Hui; Hong, Yuhao; Liu, Xiaoyu; Cai, Senrong; Duan, Jia-Ning; Yang, Junjie; Zhou, Zhiyou; Chang, Jeng-Kuei; Zheng, Mingsen; Dong, Quanfeng
Abstract : By combining steric hindrance and electrostatic repulsion, a functionalized Nafion–PEO–graphene (NPG) composite membrane was constructed and used to suppress the shuttle effect of the I − /I3 − redox couple. Abstract : Redox mediators (RMs) are widely applied in lithium–oxygen (Li–O2 ) batteries since they offer an alternative way to avoid the direct electrochemical oxidization of Li2 O2 during charging, and thus greatly reduce the charge overpotential. Unfortunately, the defenseless Li–metal anode is severely corroded by the oxidized RMs shuttled from the cathode side, resulting in the low utilization of RMs and poor cycling stability. Herein, a functionalized double-guaranteed NPG membrane with electrostatic repulsion and steric hindrance characteristics is proposed to suppress the shuttle effect of LiI RM. Benefiting from the interaction between the O atoms in PEO and the sulfonic acid groups in Nafion and the two-dimensional skeleton structure of graphene, Nafion, PEO and graphene can couple with each other, forming a large network barrier with multi-functional properties. As expected, the LiI-based Li–O2 batteries with the NPG membrane exhibited a smooth, iodine-free Li anode surface after many cycles and delivered an ultrahigh discharge capacity of ∼26 917 mA h g −1 at a current density of 200 mA g −1 and ultralong cycle life (472 cycles) at 500 mA g −1 with a cutoff capacity of 500 mA h g −1, which are far better than that of the bare batteries.